PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PADA SISWA TENTANG PERSATUAN DAN KESATUAN DI KELAS V UPT SDN 211 PINRANG - Nurjannah Nurjannah; Ritha Tuken; Al Mulky Shera (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
PThis research is motivated by the learning outcomes of students who have not reached SKBM in class V UPT SDN 211 Pinrang. The approach applied is a qualitative approach using the type of classroom action research. The subjects in this study were teachers and students of class V UPT SDN 211 Pinrang, totaling 10 students. Data collection techniques used are observation, tests, and documentation. This research was conducted in two cycles. Based on the data obtained, the results of the research in the first cycle show that the learning process is in good qualification (B), student activities are in good qualification (B) and the learning test results are in sufficient qualification (C). While in cycle II the research results on the learning process have increased with good qualifications (B), student activities are in qualification (B) and learning test results also increase to good qualifications (B). apply the make a match type cooperative learning model to the fifth grade students